031 Self awareness and insight in neuropsychiatric disorders. Issue 10 (24th September 2010) - David, A
Abstract : Abstract: The awareness of one's self as a unique sentient agent might be thought of as fundamental to mental health. Though disrupted in most if not all psychiatric disorders, it is the hallmark of depersonalisation disorder. This is a non-psychotic condition in which sufferers feel themselves to be "unreal" in some way and that their experience of the world is also unreal. Evidence suggests that part of the problem may be due to suppression of physiological arousal especially in response to emotion, which interrupts the experience of a vital sense of self, and that this maps on to lateral prefrontal and insula systems. Insight in neuropsychiatry may be thought of as a particular kind of self-awareness involving the appraisal and judgement on whether one's functions or experiences are pathological in some way. A midline cortical system has been identified as critical for self-appraisal. Lack of awareness of illness or deficits has been studied in patients with for example: schizophrenia, Alzheimer's disease and brain injury. Unawareness may apply to several domains such as social behaviour, psychopathology, memory and executive function and can be measured by different methods including discrepancy scores between patients' own and others' ratings. Our research has shown that patient groups with varying levels of deficit in each domain show varying levels of awareness. Low mood and executive impairment is associated with lack of insight in all groups while insight into memory deficits is closely tied to memory deficits themselves. We can conclude that insight is multidimensional and domain specific but that it also has associations, which are common across domains and disorders. The sense of self and awareness that one is ill or impaired appear to be separate phenomena and may relate to lateral and medial frontal executive systems, respectively.